The effect of parallax on eye fixation parameter in projection-based stereoscopic displays. - Lin, Chiuhsiang Joe; Widyaningrum, Retno (Applied Ergonomics, 2018)
The promising technology of stereoscopic displays is interesting to explore because 3D virtual applications are widely known. Thus, this study investigated the effect of parallax on eye fixation in stereoscopic displays. The experiment was conducted in three different levels of parallax, in which virtual balls were projected at the screen, at 20 cm and 50 cm in front the screen. The two important findings of this study are that parallax has significant effects on fixation duration, time to first fixation, number of fixations, and accuracy. The participant had more accurate fixations, fewer fixations, shorter fixation durations, and shorter times to first fixation when the virtual ball was projected at the screen than when it was projected at the other two levels of parallax.